Threatened species are disproportionately important interactors in a seed dispersal network in Southeast Asia. Issue 1 (7th December 2022) - Albert‐Daviaud, Aurélie; McConkey, Kim R.; Jha, Nidhi; Fontaine, Colin; Kitamura, Shumpei; Nathalang, Anuttara; Savini, Chution; Savini, Tommaso; Forget, Pierre‐Michel
Abstract: Southeast Asia is a conservation priority region due to its high biodiversity—including megafauna—and high rates of defaunation, which has negative impacts on key ecological processes such as seed dispersal. Yet, seed dispersal interactions at the community level have rarely been described in this region. This is a major knowledge gap because medium‐size and large animals are disproportionately affected by defaunation and they also have critical roles as seed dispersers. Hence, community‐wide studies that encompass a full range of animal body sizes across diverse regions are required, to enable an improved understanding of defaunation impacts. Here, we (a) describe a highly diverse Southeast Asian seed dispersal network (Khao Yai National Park, Thailand), (b) assess the role of body size in identifying important animals and (c) determine if threatened species are disproportionately important in the network. The network is highly nested and modular, with species phylogeny, body size and seed size having a major influence on modularity; mammals and birds occupied different modules. Generalist species playing important roles in the network were mainly medium or large‐sized. However, the largest disperser (elephants) played a relatively minor role in seed dispersal in this community, and bulbuls were important despite their small size. Many threatened animal species were important within the network as connector species and through their interactions with a larger number of plant species. Consequently, the resilience of this biodiversity hotspot is at threat by the potential nonrandom loss of the most important seed dispersers. Abstract : The rainforests of Southeast Asia have a high diversity of animals, many of which eat fruit and disperse the seeds of forest plants. Several large‐bodied species occur in these forests; these animals are predicted to have especially important seed dispersal roles but are also among the species most threatened by defaunation. In this study, we constructed a seed dispersal network to identify which animal species might be playing important roles in the community. We found that several threatened animal species play especially important seed dispersal roles, according to the metrics calculated from the network. Many of the important animal species were also medium to large‐bodied, but there were several exceptions to this generalization. Among the most important dispersers in the network were primates, deer, squirrels, bears, civets, hornbills, pigeons and the small‐bodied bulbuls. The potential nonrandom loss of these animals could threaten the integrity of this tropical rainforest. Abstract : 因具有极高的生物多样性（包括大型兽类），且面临能对种子传播等关键生态过程产生重要影响的动物群落的快速丧失，东南亚地区成为生物多样性保护的重要优先地区。然而，该地区在群落水平上进行种子散布相互作用的研究仍然较少。大中体型动物是关键的种子传播者，且受到更大的动物群落丧失的影响。因此，为深入了解动物群落丧失的影响，在不同地区开展涵盖各类体型动物的群落水平研究就显得十分必要。本文以泰国考艾国家公园为研究对象，旨在（a）描述这一高度多样化的东南亚种子散布网络，（b）研究体型对评估动物的种子散布功能的作用，进而（c）判断受威胁动物在种子传播网络中的作用是否更为重要。结果表明:该网络高度嵌套和模块化，且系统发育、体型和种子大小对网络模块化均有重要影响；哺乳动物和鸟类占据不同的模块。作为泛性物种的大中型动物在该网络中发挥重要作用。然而，体型最大的大象所起的种子散布作用相对较小；而体型很小的鹎类，却起到重要的作用。作为该网络中的连接物种，许多受威胁动物通过与大量植物物种的关联在该网络中起到重要作用。因此，重要种子散布动物类群的潜在非随机丧失正在对该生物多样性热点地区的群落恢复力造成威胁。